The properties of elastomers obtained with the use of carboxylated acrylonitrile-butadiene rubber and new crosslinking substances - Gaca, M.; Zaborski, M. (Polimery, 2021)
In this work, new crosslinking substances containing zinc, sodium, magnesium and aluminum ions for carboxylated acrylonitrile-butadiene rubber (XNBR) were investigated. The crosslinking density of the vulcanizates obtained was studied by equilibrium swelling in solvents. Additionally, the results confirmed the presence of ionic clusters in metal-containing XNBR vulcanizates. It was proved that these crosslinks were generated due to interactions occurring between metal ions and functional groups of rubber, namely carboxyl groups. The appearance of these unconventional crosslinks was certified by various investigations, i.e. dynamic mechanical thermal analysis (DMTA), infrared studies or equilibrium swelling of vulcanizates in toluene under ammonia treatment.